ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKUITAS MEREK UNTUK MENINGKATKAN MINAT BELI ULANG (STUDI KASUS PADA KEDAI KOPI DÔME DI SURABAYA) - Rahmawati Setyaningsih; Suyudi Mangunwihardjo; Harry Soesanto (Faculty of Economics and Business Diponegoro University, 2012)
ABSTRACT Managing brand equity has become a major issue for the marketers and marketing researches for a several decades. In service industry, such as hospitality, company can encourage customer repatronage intention through high brand equity it has. The problem of this research is how to improve brand equity that affects repatronage intention. The reseacher has developed a model and four hypotheses that have been proposed in this research. The sampling technique used is purposive method. Sample used in this research is 120 respondents in which the visitors of DOME coffee shops at Surabaya. The data analysis that is used in this research is Structural Equation Modelling (SEM) in AMOS 7.0 program. The result of SEM analysis has fullfiled the Goodness of Fit Index Criteria which are: chi square = 129,585; probability = 0,123; GFI = 0,887; AGFI = 0,846; CFI = 0,976; TLI = 0,971; RMSEA = 0,036 and CMIN/DF = 1,140. It has been discovered that there is only three out of four hypotheses are accepted. Here are the result of those four hypotheses: 1. Country of origin perception has positive and significant effect on brand equity, 2. Sales promotion has positive and significant effect on brand equity, 3. Physical environment does not have any effect on brand equity, and 4. Brand equity has positive and significant effect on repatronage intention. Keywords : Country of origin perception; sales promotion; physical environment; brand equity; repatronage intention; coffee shops